The bohemians : a novel - Darznik, Jasmin, 1973- (Ballantine Books, 2021)
"A dazzling novel of one of America's most celebrated photographers--exploring Dorothea Lange's wild years in San Francisco that awakened her career-defining grit, compassion, and daring. In 1918 Dorothea leaves the East Coast for California, where a disaster kick-starts a new life. Her friendship with Caroline Lee, a vivacious, straight-talking woman with a complicated past, gives her entrée into Monkey Block, an artists' colony and the bohemian heart of San Francisco. Dazzled by Caroline and her friends, Dorothea is catapulted into a heady new world of freedom, art, and politics. She also finds herself unexpectedly--and unwisely--falling in love with Maynard Dixon, a brilliant but troubled painter. Dorothea and Caroline eventually create a flourishing portrait studio only to have a devastating betrayal push their friendship to the breaking point and alter the course of their lives. Rich with descriptions of San Francisco in the glittering and gritty 1920s, and with cameos from such legendary figures as Mabel Dodge, Frida Kahlo, Ansel Adams, and DH Lawrence, The Bohemians explores the gift of friendship, the possibility of self-invention, and the ferocious pull of history"--